'How I Feel About My School': The construction and validation of a measure of wellbeing at school for primary school children. (January 2018) - Allen, Kate; Marlow, Ruth; Edwards, Vanessa; Parker, Claire; Rodgers, Lauren; Ukoumunne, Obioha C; Seem, Edward Chan; Hayes, Rachel; Price, Anna; Ford, Tamsin
There is a growing focus on child wellbeing and happiness in schools, but we lack self-report measures for very young children. Three samples ( N  = 2345) were combined to assess the psychometric properties of the How I Feel About My School (HIFAMS) questionnaire, which was designed for children aged 4–8 years. Test–retest reliability was moderate (intraclass correlation coefficient = .62). HIFAMS assessed a single concept and had moderate internal consistency (Cronbach's alpha values from .62 to .67). There were low correlations between scores on the child-reported HIFAMS and parent and teacher reports. Children at risk of exclusion had significantly lower HIFAMS scores than the community sample (mean difference = 2.4; 95% confidence interval (CI) = [1.6, 3.2]; p  < .001). Schools contributed only 4.5% of the variability in HIFAMS score, the remaining 95.5% reflecting pupil differences within schools. Girls' scores were 0.37 units (95% CI = [0.16, 0.57]; p  < .001) higher than boys, while year group and deprivation did not predict HIFAMS score. HIFAMS is a promising measure that demonstrates moderate reliability and discriminates between groups even among very young children.